Revitalizing Nepal’s National Security Council and its Secretariat in a Changing Geo-Political Context (Unity Journal, 2025)
Security has evolved to become multidimensional and comprehensive in a competitive geopolitical scenario, demanding an effective institutional setup. Nepal’s National Security Council is mandated to recommend the Government of Nepal for formulating policy in the overall national interest. Since its inception, there has been much debate on the work of the Council and its Secretariat. However, a prominent gap exists in Nepali literature regarding the effectiveness of the work of the council and secretariat. This article advocates for a strong NSC architecture as an oversight agency for policy implementation in the defense and security sector in Nepal. Thus, the research topic is worth examining in a rapidly changing global and regional security milieu. This paper aims to explore the current setup of the Council and Secretariat by analyzing its importance for Nepal, which has many security sensitivities. The paper employs a qualitative research approach, and analytical methods are used. Identifying different geostrategic challenges Nepal has faced in recent times, this article also argues that there is a need for urgent revitalization of this body through legislative reforms and a determined will to fulfill the constitutional mandate. This important body needs to be reinvigorated because of geopolitical challenges that are rapidly increasing in a complex and volatile world whose impacts can be seen in Nepal.